Interest Rate and Exchange Rate Volatility Spillovers: Multiscale Perspective of Monetary Policy Transmission in Ghana - Nana Kwame Akosah; Paul Alagidede; Eric Schaling (Journal of Central Banking Theory and Practice, 2020)
Ghana's economy is characterised by acute exchange rate volatility alongside persistent and high consumer inflation. This places the economy among the sub-Saharan African countries with the highest inflation over the years. Therefore, we explore in-sample and out-of-sample macro-volatility spillovers to determine the effectiveness of monetary policy and also ascertain the relevance of the exchange rate in Ghana's interest rate setting at both time and multiscale domains. The study reveals scale-dependent interconnectedness among the macro-variables as their causal linkages broadly intensify at the longer time-scale. We find the real policy rate and the exchange rate to be net transmitters of shocks, while inflation and output gaps are net receivers of shocks from the system. Output gap, however, is the largest net receiver of shocks from the system. The empirical findings generally buttress the prerequisite to uphold exchange rate stability in order to inure general macroeconomic stability in Ghana. In addition, the extent of spillover dynamics from policy interest rate to and from the targeted macro-variables (particularly output gap and inflation) appears to be moderate even in the long run, surmising less effective monetary policy transmission in Ghana.
Keywords: C32; E42; E43; E47; E52; E58; F31; F41; 330; Volatility Spillover; Nonlinear Causality; Variance Decomposition; Multi-scale.